2017
DOI: 10.18869/acadpub.hmj.20.6.401
|View full text |Cite
|
Sign up to set email alerts
|

The comparison effects of eight weeks spark and frenkel exercises on static and dynamic balance in the blinds

Abstract: Original ArticleAbstract Introduction: One of the most important human senses is vision, which its loss is causing many primary and secondary complications for physical and psychological health such as difficulties in static and dynamic balance. This study aimed to compare the effect of 8 weeks of Spark and Frenkel exercises training on the static and dynamic balance in blind people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Studies show that training and rehabilitation protocols decrease imbalance and can be used as a strong interventive treatment for children with visual disorder and balance dysfunction. The review of the literature showed that all training, rehabilitation, and exercise programs positively affected the balance improvement in the blind [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Mobility is one key element in these protocols because a sedentary lifestyle explains a certain aspect of imbalance in the blind population.…”
Section: Effects Of Training Protocols On Balance In the Blindmentioning
confidence: 99%
“…Studies show that training and rehabilitation protocols decrease imbalance and can be used as a strong interventive treatment for children with visual disorder and balance dysfunction. The review of the literature showed that all training, rehabilitation, and exercise programs positively affected the balance improvement in the blind [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Mobility is one key element in these protocols because a sedentary lifestyle explains a certain aspect of imbalance in the blind population.…”
Section: Effects Of Training Protocols On Balance In the Blindmentioning
confidence: 99%
“…Balance is an essential component of any motor system; it is one of the most important factors in the sensory-motor system modulating the complex relationship between sensory inputs and required motor responses. Balance is one of the key and integral components in daily activities (Rajabi, Goodarzi, and Mazidi 2017). It is an essential factor for the blind that helps to create spatial integration in them (Çolak et al 2004).…”
Section: Introductionmentioning
confidence: 99%